Influence of Internet Use on Commercial Health Insurance of Chinese Residents - Bao-Chang Xu; Xiao-Ni Xu; Jin-Chun Zhao; Meng Zhang (Frontiers Media S.A., 2022)
As a necessary supplement to social medical insurance, commercial health insurance is an important part of the Healthy China strategy. This study, based on the Chinese General Social Survey (CGSS) data in 2017, uses the probit model to analyze and study the internal relationship between Internet use and commercial health insurance purchase of urban and rural residents. The research results show that the use of the Internet significantly promoted commercial health insurance purchases of residents, and the promotion effect for rural residents is apparently better than that among urban residents. In addition, the social level of residents is improved through the use of Internet, which can promote commercial health insurance purchases. It provides a significant reference value for the effective integration of Internet use and commercial health insurance, and the high-quality development of the modern insurance industry.